(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Cochlear implants can fill your world with the joy of sound. A cochlear implant can help you or your child hear better in everyday life. Getting a cochlear implant is a big decision, but it can change your life. In this article, we will get the necessary knowledge about the use of the structure of the cochlear implant. Cochlear implants are a device that provides excellent hearing quality and excellent reliability.